Constitutional and Political Developmemt in Pakistan: A Review of the Legislative Performance Of the 14th National Assembly(2013-2018) - Bashir, Hammad; Khan, Abdul Basit; Ashraf, Muhammad Javed (Annals of Human and Social Sciences, 2024)
During the tenure of 14th National Assembly of Pakistan many innovative laws and political reforms related to different disciplines of life were introduced and executed. The size of legislation was enlarged mainly due to the coordination and healthy consensus of both the treasury benches and opposition parties portraying a high level of their political maturity. In this tenure the PML-N-led Government incorporated five constitutional amendments. This period was also marked by efforts to strengthen democratic institutions, enhancing legislative frameworks, and addressing some ever-demanding socio-economic challenges. The current study provides a deep insight into performance and achievements by the National Assembly during this period and highlights some of the significant institutional and political developments and their impact on the progress and performance of the political system at large. It also examines the functioning of the Federal Legislature during the period of Pakistan Muslim League-Nawaz (PML-N) to assess whether the Assembly effectively represented the general will by formulating public policies or merely acted as a debating chamber. Furthermore, it presents an analysis of the effectiveness of the committee system and the growing role of the opposition, which not only significantly improved the legislative efficiency of the assembly but also fostered cooperation and trust between the government and the opposition parties. The study recommends that the footprints of the exemplary cooperation of the ruling elite exhibited during the time period under examination must be followed by future legislators to achieve an ever-prospering democratic Pakistan.